(untitled) (Fiep Bulletin - online, 2014)
College students belong to a group with a high probability of presenting excessive daytime sleepiness and poor sleep quality, taking into account school schedules, as they, in an attempt to fulfill their activities by alternating day and night, causing problems with regularity of sleep, which coupled with lack of physical activity practice, can bring harm to their health. The purpose of this descriptive study was to evaluate the quality of sleep and physical activity of 66 university students of both sexes, aged between 17 and 40 years enrolled in the 1st, 3rd, 5th and 7th semesters in the Physical Education Course at State University of Rio Grande do Norte in the town of Mossoró-RN, being used as tools to assess a questionnaire of Pittsburgh sleep quality index (PSQI), and International physical activity questionnaire short version (IPAQ). The statistic used to verify normality was the Komolgorov Smirnov test, for parametric variables we used Man-Whitney, for the nonparametric variables we used the Kruskal Wallis tests with significance level of p <0.05, the software used for statistical analysis was SPSS 20.0, Portuguese version. The analyzed data showed that the majority of students from the Physical Education Course present a poor quality of sleep, while maintaining continuous physical activity practice.